Distribution, abundance and dynamics of the House Sparrow "Passer domesticus" in Berlin - Böhner, Jörg; Witt, Klaus (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The paper summarizes the current knowledge on the distribution, abundance and dynamics of the House Sparrow "Passer domesticus" in Berlin, the German capital with a size of 892 km2 and about 3.4 million inhabitants. Main sources of information are studies conducted by the Berlin Ornithological Working Group (BOA), and its predecessors in the formerly divided Berlin, which include two large atlas works, a detailed grid-net census in the south-western part, two large-scale breeding season counts, continuous winter counts, as well as several smaller investigations on the species` abundance at specific sites in the city.
Keywords: wróblowe; ornitologia; Niemcy; czasopismo